Micro- and nanoplastics in the environment: research and policymaking - Costa, João Pinto da (2020)
Initial reports on the presence of microplastics in the Ocean date from the 1970's. In spite of the noted potential risks these debris posed to both the environment and humans, the scientific community paid little attention to then raised alarms. Recently, however, there has been an increasing interest by both the general public and the scientific community in the contamination and pollution of the marine environment by micro- and nanoplastic particles. Due to their physical and chemical characteristics, these pervasive contaminants can be found across the Globe and are distributed across the water column and have been shown to be ingested by numerous organisms. Although generally considered biochemically inert, such materials can adsorb other chemical substances, such as persistent organic pollutants (POPs), hence potentially leading to bioaccumulation and bioamplification phenomena. However, despite this recognized harmfulness, and although microplastics are a recognized threat to the “Blue Economy”, there are still multiple research gaps that should be adequately addressed, in order to obtain a realistic assessment of their prevalence in the environment. Additionally, despite the numerous national, regional and international regulatory instruments aiming at reducing the contamination by plastic litter, these appear to have been, so far, insufficient for reaching their proposed goal. Herein, the current gaps in micro- and neoplastic research and regulation are evaluated and some suggestions for overcoming such limitations are proposed.